1991
DOI: 10.1128/aem.57.12.3489-3495.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Rhizobium leguminosarum bv. Trifolii Strains Revealed by Allozyme and Restriction Fragment Length Polymorphism Analyses

Abstract: Allozyme electrophoresis and restriction fragment length polymorphism (RFLP) analyses were used to examine the genetic diversity of a collection of 18 Rhizobium kguminosarum bv. trifolii, 1 R. kguminosarum bv. viciae, and 2 R. meliloti strains. Ailozyme analysis at 28 loci revealed 16 electrophoretic types. The mean genetic distance between electrophoretic types of R. leguminosarum and R. meliloti was 0.83. Within R. keguminosarum, the single strain of bv. viciae differed at an average of 0.65 from strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…1991). Two cloned chromosomal DNA fragments were used as probes: recombinant plasmid pRtlOl3, which contains a repeated DNA sequence and cosmid pIM178, which contains part of an ATPase structural gene (Demezas et al 1991) (see Fig. 1).…”
Section: Restriction Fragment Length Polymorphism Analysismentioning
confidence: 99%
“…1991). Two cloned chromosomal DNA fragments were used as probes: recombinant plasmid pRtlOl3, which contains a repeated DNA sequence and cosmid pIM178, which contains part of an ATPase structural gene (Demezas et al 1991) (see Fig. 1).…”
Section: Restriction Fragment Length Polymorphism Analysismentioning
confidence: 99%
“…Moreover, the establishment of symbiosis is controlled by the abundance, viability and infectivity of natural populations of rhizobia (Bottomley, 1992). Different studies indicated that the genetic diversity of natural populations of rhizobia could also be affected by the site of origin and by host plant factors (Demezas et al, 1991;Paffetti et al, 1998;Carelli et al, 2000;Palmer & Young, 2000;Andronov et al, 2001;Bromfield et al, 2001;Zhang et al, 2001;Laguerre et al, 2003). The adaptation of the rhizobial populations to a particular environment not only affects the genetic structure of the population but it can also mould the phenotypic traits of the strains, a phenomenon particularly relevant for traits such as salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conservative nature of the 16s rRNA genes limits the discriminatory power of the method for distinguishing closely related strains. T h e discrimination of rhizobial strains can be achieved by other molecular techniques such as classical RFLP, which is based on Southern hybridization (Demezas et al 1991), and also by a direct RFLP analysis of 16s rDNA amplificates (Armarger et al 1994;Laguerre et al 1994). However, discrimination of closely related strains by these methods requires the application of several probes and/or several restriction endonucleases.…”
Section: Introductionmentioning
confidence: 99%